Mejora de la comunicación a través de una red integral corporativa de información entre los locales descentralizados de la municipalidad provincial de Alto Amazonas – Yurimaguas - Morales Silva, Ángel Armando (2013)
The present Thesis, "IMPROVING COMMUNICATION THROUGH A COMPREHENSIVE CORPORATE INFORMATION NETWORK AMONG LOCAL MUNICIPALITY DECENTRALIZED AMAZON PROVINCIAL HIGHYURIMAGUAS"; has general goal, improve communication between decentralized local Municipality Provincial Alto Amazonas Yurimaguas through a Corporate Integrated information Network which allows an efficient and timely information between various managements and / or areas of the organization to improve their performance to the public. It also has specific objectives, diagnose the present reality of the administrative processes and communication between decentralized local Provincial Municipality of Alto Amazonas, Designing a Comprehensive Corporate Information Network by Top Dow Methodology; implement comprehensive network among local corporate decentralized to the provincial municipality of Alto Amazonas - Yurimaguas, for efficient local communication between different decentralized so as to save resources and time. For the development of the proposal using different methodologies. For information gathering techniques were observation, interviews, as well as the review and evaluation of documents, for the analysis and design methodology was used Network Design Top-Dow. Having the need to improve administrative processes and communication between decentralized local Provincial Municipality of Alto Amazonas, and thus achieve greater prestige of the institution with the implementation of a comprehensive corporate network of reliable and timely transmission and communication; this project aims to improve and optimize the communication of the Provincial Municipality of Alto Amazonas Yurimaguas through comprehensive corporate network information